Electrochemical and microbiological response of exoelectrogenic biofilm to polyethylene microplastics in water. (1st March 2022) - Wang, Song; Xu, Mingyi; Jin, Biao; Wünsch, Urban J.; Su, Yanyan; Zhang, Yifeng
Highlights: First study of the response of exoelectrogenic biofilm to microplastics. Polyethylene microplastics declined current density of microbial electrolysis cell. Polyethylene microplastics inhibit the cell viability, increased dead cell ratio. Extracellular polymeric substances declined with the occurrence of microplastics. Extracellular electron transfer related genes and cytochrome c decreased. Abstract: Exoelectrogenic biofilm and the associated microbial electrochemical processes have recently been intensively studied for water treatment, but their response to and interaction with polyethylene (PE) microplastics which are widespread in various aquatic environments has never been reported. Here, we investigated how and to what extent PE microplastics would affect the electrochemistry and microbiology of exoelectrogenic biofilm in both microbial fuel cells (MFCs) and microbial electrolysis cells (MECs). When the PE microplastics concentration was increased from 0 to 75 mg/L in the MECs, an apparent decline in the maximum current density (from 1.99 to 0.74 A/m 2 ) and abundance of electroactive bacteria (EAB) in the exoelectrogenic biofilm was noticed. While in the MFCs, the current output was not significantly influenced and the abundance of EAB lightly increased at 25 mg/L microplastics. In addition, PE microplastics restrained the viability of the exoelectrogenic biofilms in both systems, leading to a higher system electrode resistance. Moreover, the microbial community richness and the microplastics-related operational taxonomic units decreased with PE microplastics. Furthermore, the electron transfer-related genes (e.g., pil A and mtr C) and cytochrome c concentration decreased after adding microplastics. This study provides the first glimpse into the influence of PE microplastics on the exoelectrogenic biofilm with the potential mechanisms revealed at the gene level, laying a methodological foundation for the future development of efficient water treatment technologies. Graphical abstract: Image, graphical abstract